Research on hot water chemical flooding technology in Bohai heavy oil field - Jian, Zhang; Dan, Liang; Wensheng, Zhou; Qichen, Zhang; Liqi, Wang; Zhijie, Wei (Frontiers in Energy Research, 2024)
Based on the geological reservoir parameters of Bohai B Oilfield, taking the enhanced oil recovery and comprehensive economic indicators as the objective functions, the oil displacement system evaluation experiment and scheme design research were carried out, and the injection parameters such as the temperature of hot water, the concentration of chemical agent and the amount of chemical agent that affect the effect of hot water chemical flooding were optimized. The results show that with the increase of temperature, the effect of chemical agents on improving the water-oil mobility ratio and reducing the viscosity of crude oil is weakened, and the thermal energy plays a leading role in enhancing oil recovery, but when the temperature is higher than 115℃, the improvement of oil recovery is slowed down, and the comprehensive economic indicators decline rapidly. As the concentration of chemical agent increases, the enhanced oil recovery increases monotonously. When the concentration is 1500 mg/L, the comprehensive economic indicators reach the peak and then decline, indicating that the efficiency of chemical agent decreases. The total amount of chemical agent shall be controlled within 0.25 0.30PV. The case calculation shows that hot water chemical flooding can expand the effective radius from 80m to 400m, more effectively use the reserves between injection and production wells, increase the oil recovery by 4.8 percentage points, and increase the oil yield by 31.7m 3 /t per ton of agent. It is suggested that Bohai B Oilfield can adopt hot water chemical flooding after the multiple thermal fluid huff and puff to continuously guarantee the oilfield production.